Optimization of Learning Physical Education In Digital Era: A Systematic Review - Nursandi Mulato; Furqon Hidayatulloh; Sapta Kunta Purnama; Rony Syaifullah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
In the digital era, the evolution of physical education is imperative to meet the changing technological landscape. This study aims to explore strategies for enhancing physical education learning by integrating technology to foster student motivation and participation. Employing a systematic review with the PRISMA framework, we critically examined the intersection of technology and physical education. Our findings reveal that a multifaceted approach involving educational management, cooperative and blended learning, and curriculum innovation is essential. We also recognize the challenges and potential drawbacks of digitalization, ensuring a balanced perspective. The study concludes that optimizing physical education in the digital age requires not only embracing technological advancements but also addressing their complexities to enrich the learning experience.